The social mythology of medieval Icelandic literature - Avis, R; Robert Avis (2011)
This thesis argues that the corpus of Old Norse-Icelandic literature which pertains to Iceland contains an intertextual narrative of the formation of Icelandic identity. An analysis of this narrative provides an opportunity to examine the relationship between literature and identity, as well as the potency of the artistic use of the idea of the past. The thesis identifies three salient narratives of communal action which inform the development of a discrete Icelandic identity, and which are examined in turn in the first three chapters of the thesis. The first is the landnám, the process of settlement itself; the second, the origin and evolution of the law; and the third, the assimilation and adaptation of Christianity. Although the roots of these narratives are doubtless historical, the thesis argues that their primary roles in the literature are as social myths, narratives whose literal truth- value is immaterial, but whose cultural symbolism is of overriding importance. The fourth chapter examines the depiction of the Icelander abroad, and uses the idiom of the relationship between þáttr (‘tale’) and surrounding text in the compilation of sagas of Norwegian kings Morkinskinna to consider the wider implications of the relationship between Icelandic and Norwegian identities. Finally, the thesis concludes with an analysis of the role of Sturlunga saga within this intertextual narrative, and its function as a set of narratives mediating between an identity grounded in social autonomy and one grounded in literature. The Íslendingasögur or ‘family sagas’ constitute the core of the thesis’s primary sources, for their subject-matter is focussed on the literary depiction of the Icelandic society under scrutiny. In order to demonstrate a continuity of engagement with ideas of identity across genres, a sample of other Icelandic texts are examined which depict Iceland or Icelanders, especially when in interaction with non-Icelandic characters or polities.